Job Description of Community Police Officers of the National Police of Ukraine - V. I. Barko; V. V. Barko (Law and Safety)
The authors have studied the problems of theoretical principles and methodical tools of carrying out professional research at the National Police of Ukraine, in particular, the issue of developing a job description of community police officers. It has been demonstrated that job descriptions represent a complete description of the specifics of a particular profession, they reveal the content of professional work, as well as the requirements that a profession brings to a person; this is a document that provides a comprehensive, systematic and comprehensive description of the objective characteristics of the profession and the totality of its requirements to individual and psychological features of a man. An important part of the job description is a psychic profile containing a complete description of the actual psychological characteristics and professionally important personal qualities of specialists.